Interdisciplinary Networks and Reflection on Pedagogical Practice - Branco Vidal Bustamante, Silvia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this study, knowledge networks and their following related actions at school are analyzed: the use of new technologies, making possible rethink the role of the school, traditionally linked to the transfer of content and information; the interdisciplinary approach to the knowledge, presenting an heterarchical design, with different but related elements in scope and depth, like the elements of a web or a large network; the reflection on action in pedagogical practice, whose rupture takes place with the intervention of technology and the teacher playing the role of mediator.